Assessment of forest visitors' route preferences – Impact encounters across a range of forest environments. (December 2021) - Skov-Petersen, H.; Jensen, F.S.; Jacobsen, J.B.
Abstract: Studies of visitors' preferences for forest environments play a central role for the understanding of recreational behaviour. The encounter of other agents, such as wildlife or other visitors, has proven important for preferences, and this is something visitors may affect themselves. Thus, this study focusses on forest visitors' preferences for forest environments and potential encounters with other agents. 1089 respondents have been asked to consider a choice for change of direction at trail junctions, during a visit to the forest, by ranking five cards representing possible path segments. Each segment constituted a given forest environment (represented by text and a photo) and agent types and numbers (text and an icon), and the direction (text only) – relative to a preferred direction. Results show that on average respondents will detour from their preferred direction, disregarding the forest environment, to experience wildlife. At the other end of the scale, larger groups of mountain bikers or runners can make respondents detour in all forest environments, except for the most preferred ones, to avoid an encounter. Based on a latent class analysis three classes are identified with distinct preferences. 20% of the respondents are unlikely to detour no matter the possible forest environment or agent types. 30% are not affected by encountering other agents, but are to a slight but significant extent affected by the forest environment. The majority, constituting 50% of the population, is strongly influenced by forest environments and even more by potential encounters with other agents. Results largely confirm earlier studies using an ordinal scale, but in addition, we estimate the mutual strength of the preferences and thereby allowing for better guidance of how to manage for forest recreation. Management implications: In our study, a large group of people state that encountering other types of visitors or wild life matters a lot, and often overrules, the diverse utility of different forest environments. This highlights the necessity of focusing on the management trade-offs between nature conservation and recreational use. Abstract : One implications of our study relates to path network planning. In areas with less preferred forest environments (e.g. as present in afforestation areas), path segregation may be more important than in the more preferred (e.g. older, more consolidated) areas, where encounters with other visitors have less negative influence on visitors utility.